COMPUTER NETWORKS AND THEIR BASIC CONCEPTS - Madirimova Saodatjon Madirimovna; Annazarova Barno Rustamovna; Otajonova Gulhayo Maqsud’s daughter (Galaxy International Interdisciplinary Research Journal, 2022)
This article describes the types of regional support of computer networks, the importance of files in the computer program, the relationship between user and computer, file-server and client-server differences and their basic classifications. This article also covers the principles of network interconnection.